Improving Al-Imam Al-Mandhari the Hadiths with evidence: تحسين الإمام المنذري للحديث بالشواهد (المجلة العربية للعلوم و نشر الأبحاث, 2017)
The research dealt with ashort translation of Imam Zaki al-DinAbi Muhammad Abd al-Azim ibnAbd al-Qawi al- mundhiri. He reveald his method of improving the hadiths with evidence that was agreed upon by al-Bukaari andMuslim or with more than one witness in al-Saheehayn. The search also revealed the navigation of Imam al-Manzari in modern science and his highaccuracy in criticizing the hadiths.